International Editorial Board of vol. 25 No. 1 (2023): Journal Scientific and Applied Research: International Editorial Board of vol. 25 No. 1 (2023): Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
International Editorial Board of vol. 25 No. 1 (2023): Journal Scientific and Applied Research